Constitutive, institutive and up-regulation of carotenogenesis regulatory mechanism via in vitro culture model system and elicitors - Othman, Rashidi; Mohd Hassan, Norazian; Mohd Zaifuddin, Fatimah Azzahra (Universiti Kebangsaan Malaysia (UKM), 2015)
Phytohormone abscisic acid (ABA) plays a regulatory role in many physiological processes in plants and is regulated and controlled by specific key factors or genes. Different environmental stress conditions such as water, drought, cold, light, and temperature result in increased amounts of ABA. The action of ABA involves modification of gene expression and analysis of in vitro callus model system cultures revealed several potential of constitutive, institutive and up-regulation acting regulatory mechanisms. Therefore, this study was aimed at establishing in vitro cultures as potential research tools to study the regulatory mechanisms of the carotenoid biosynthesis in selected plant species through a controlled environment. The presence and absence of zeaxanthin and neoxanthin in callus cultures and intact plants could be explained by changes in gene expression in response to stress. Abiotic stress can alter gene expression and trigger cellular metabolism in plants. This study suggested that the key factors which involved in regulatory mechanisms of individual carotenoid biosynthesis in a particular biology system of plants can be either be silenced or activated. Therefore, based on the results in this study environmental stress is made possible for enhancement or enrichment of certain carotenoid of interest in food crops without altering the genes.